Recurrent furunculosis: Efficacy of the CMC regimen — skin disinfection (chlorhexidine), local nasal antibiotic (mupirocin), and systemic antibiotic (clindamycin). (November 2013) - Davido, Benjamin; Dinh, Aurélien; Salomon, Jérôme; Roux, Anne Laure; Gosset-Woimant, Marine; Pierre, Isabelle; Perronne, Christian; Bernard, Louis
Abstract Background: The treatment of recurrent furunculosis is poorly documented and represents a public health challenge. The medical care of this disease is often disappointing, especially as the disease evolution is uncertain and relapses occur. We report the efficacy and safety of our CMC regimen: skin disinfection (chlorhexidine), local nasal antibiotic (mupirocin), and systemic antibiotic (clindamycin). Methods: Patients attending our institution during the period 2006–2012 for recurrent furunculosis (≥ 4 episodes/y) were enrolled in the study. Clinical and bacteriological data were collected. Staphylococcus aureus colonization was also investigated in close contacts, and carriers were treated. Patients were treated with the CMC regimen: skin disinfection with chlorhexidine for 21 days, nasal mupirocin ointment for 5 days, and oral clindamycin 1800–2400 mg for 21 days. Results: Nineteen patients were included. Their mean age was 36 ± 14.5 y and the male to female sex ratio was 1.1. Screening swabs from all sites were S. aureus-positive in 63% (n = 12), including 4 methicillin-resistant S. aureus (MRSA). Before the CMC regimen, the median time to relapse was 31 days (mean 52 days). The mean number of recurrences was 5.5 ± 2.4/y. After the CMC regimen, among 16 patients who had a complete follow-up, 14 were healed beyond 9 months. Two recurrences occurred, 1 in an MRSA carrier and 1 in a patient with an insufficiently treated dermatosis. No serious side effect occurred that required the cessation of treatment. Conclusions: There are 2 major routes involved in recurrent furunculosis: risk factors and staphylococcal colonization of close contacts. Our procedure is safe and effective, with 87% remission beyond 9 months. It merits testing on larger numbers of participants.